2013
DOI: 10.1002/pds.3507
|View full text |Cite
|
Sign up to set email alerts
|

Off‐label use of second generation antipsychotics for post‐traumatic stress disorder in the Department of Veterans Affairs: time trends and sociodemographic, comorbidity, and regional correlates

Abstract: Post-traumatic stress disorder population growth is driving substantial increases in SGA use. Decreasing rates of the Department of Veterans Affairs prescribing may be due to integrated system-wide mechanisms (e.g., national practice guidelines), although regional variations remain prominent. These analyses provide foundational steps for identifying modifiable provider-level and organization-level determinants of SGA prescription in this growing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…[24][25][26][27] Contrary to our second hypothesis, inclusion of access factors in the model did not significantly impact the odds of pharmacotherapy retention among African American and Latino Veterans. [61,62] If so, then our findings may significantly underestimate the racial/ethnic disparity in PTSD treatment in the VA. It may be that inclusion of access factors failed to influence variation in treatment retention rates across groups because we sampled only Veterans already using VA services.…”
Section: Discussionmentioning
confidence: 84%
“…[24][25][26][27] Contrary to our second hypothesis, inclusion of access factors in the model did not significantly impact the odds of pharmacotherapy retention among African American and Latino Veterans. [61,62] If so, then our findings may significantly underestimate the racial/ethnic disparity in PTSD treatment in the VA. It may be that inclusion of access factors failed to influence variation in treatment retention rates across groups because we sampled only Veterans already using VA services.…”
Section: Discussionmentioning
confidence: 84%
“…Latino veterans with PTSD appear to access treatment at similar rates as non-Latino White veterans with PTSD [69,70]. Latino veterans with PTSD are more likely than non-Latino White veterans with PTSD to receive second-generation antipsychotics [71] and other psychotropic medication [72]. They were also more likely to have been treated in traditional long-term inpatient programs, be in treatment groups longer, spend more time in abreactive treatment modalities and be more satisfied with their treatment than non-Latino White veterans [72,73].…”
Section: Resultsmentioning
confidence: 99%
“…Research on prescription drug use in veterans with PTSD and substance use disorder has, thus far, largely focused on opioids, benzodiazepines, and antipsychotics (Bauer et al, 2014;Hawkins, Malte, Imel, Saxon, & Kivlahan, 2012;Sernyak, Kosten, Fontana, & Rosenheck, 2001;Whitehead et al, 2008). There has been considerable debate on the safety and efficacy of these drugs for veterans with PTSD, and one small study found PTSD to be associated with an increased likelihood of medication underuse, abuse, and treatment non-adherence in different patients (Lockwood, Steinke, & Botts, 2009).…”
mentioning
confidence: 96%
“…Veterans with PTSD frequently receive medications not recommended for people with this disorder, including atypical antipsychotics in both male and female veterans and benzodiazepines in female veterans with PTSD . Bauer et al (2014) evaluated factors that were associated with off-label atypical antipsychotic use in veterans with PTSD and found that having a diagnosis of substance use disorder increased the likelihood of being prescribed these medications. Such use of psychotropic medications without specific justification may pose important side effect risks (for example metabolic syndrome) in the absence of evidence of outcome benefits.…”
mentioning
confidence: 99%